A mini review and bibliometric analysis of palm oil mill effluent in past five years. Issue 1 (1st February 2023) - Mohd Pauzi, F; Muda, K; Basri, H F; Omoregie, A I; Hong, C Y; Aftar Ali, N S; Mohamed Najib, M Z; Mohd Amin, M F; Ismail, S; Mohamad Shahimin, M F; Dahalan, F A
Abstract: Indonesia and Malaysia are countries with the highest palm oil production globally. Indonesia is leading the list, followed by Malaysia and Thailand. Palm oil production generates countless benefits to the economy, environment, and society of the contributed countries. This industry provides high income and collection of methane gas for biogas generation and economy of the local community. However, despite the benefits, this industry has some difficulties, including treating the Palm Oil Mill Effluent (POME). POME contains a complex microbial structure and a high amount of oil, grease, and suspended solids. The existing treatment of POME consists of many drawbacks that lead to poor quality of the effluent and failure to meet the minimum requirement from the Department of Environment (DOE). Advance Oxidization Process (AOP), bio granulation, and ponding system are among the research that have been tried to treat POME. The local government still uses old-style treatment types such as Conventional Activated Sludge (CAS), ponding system, and anaerobic digester tank. This review paper presents a mini review of positive and negative consequences the palm oil industry as well as examine a bibliometric study towards the modern research development of the POME. This mini review concludes that the palm oil industry encourages the positive impact in economy, environment and social to the many parties especially country and local community. Besides that, the existing treatment of the POME have to be improved appropriate with the increment of the demand and era.